2019
DOI: 10.1002/macp.201900084
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processable Conductive Organics via Anion‐Induced n‐Doping and Their Applications in Organic and Perovskite Solar Cells

Abstract: The essential challenge for accessing high‐performance organic optoelectronics strongly relies on how to enable organic materials with high charge transport capabilities. This short review gives an elucidation of the mild n‐doping that occurs between Lewis base anions and n‐semiconductors, as well as their extension to develop solution‐processable conductive interlayers for organic and perovskite solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 104 publications
(206 reference statements)
1
13
0
Order By: Relevance
“…Meanwhile, the gap state of DOS is almost eliminated for ionic bonding, which indicates a facilitated charge transfer between the perovskite and fulleropyrrolidium iodide. 28,46 This is further confirmed by the Bader charge analysis results that charge transfer between the ionic fullerene and perovskite surface is about 0.14 electrons per fullerene molecule, compared with negligible transfer between the fulleropyrrole and FAPbI 3 . Similar results can be readily observed in an increase of wave function overlap that bridges the trap states induced by both positive and negative charge defects (Figure 2e).…”
supporting
confidence: 63%
“…Meanwhile, the gap state of DOS is almost eliminated for ionic bonding, which indicates a facilitated charge transfer between the perovskite and fulleropyrrolidium iodide. 28,46 This is further confirmed by the Bader charge analysis results that charge transfer between the ionic fullerene and perovskite surface is about 0.14 electrons per fullerene molecule, compared with negligible transfer between the fulleropyrrole and FAPbI 3 . Similar results can be readily observed in an increase of wave function overlap that bridges the trap states induced by both positive and negative charge defects (Figure 2e).…”
supporting
confidence: 63%
“…The UV–vis spectra already showed charge transfer character of the complex formation. Meanwhile, some recent literature showed that large, electron-deficient aromatic systems could facilitate an anion-induced electron transfer process. , We wondered if this process could occur in our system with that the electron transfer from N 3 – to the BTI cage 4 produces radical components 4 •– and N 3 • . To check this possibility, some preliminary EPR experiments were performed to probe the possible radical species.…”
mentioning
confidence: 98%
“…An NIR active layer of the PM6:Y6 blend (SI) is employed . Bis-FIMG (SI) is a self-doped conductive bifunctional fulleropyrrolidinium iodide as an electron-transport layer. , The F–P resonant-cavity electrode consists of a Ag–TeO 2 –Ag structure, wherein TeO 2 with a refractive index ( n ) of 2.2, as the dielectric material, ensures good light transmission at the metal/dielectric interfaces; meanwhile, its near-zero extinction coefficient ( k ) minimizes the intrinsic absorption in the F–P electrode. The n and k values of the active layer and TeO 2 are presented in Figure S1.…”
mentioning
confidence: 99%